(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
With the aim to gain an appreciation of how nature insulates animal bodies with furs, in this exploratory study we investigated the TC and morphology of natural and synthetic fibrous materials. Specifically, we present our experimental observations on coyote, wolverine, and synthetic furs, as well as Polyacrylonitrile (PAN) nanofibers and knitted fabric. The TC was measured at a temperature range of 221210 25e6C to 65 25e6C. The natural furs consist of fibers with different diameters and cuticular scale patterns. They form coreshell fibers with complex cellular structures in the core. The natural furs have lower TC compared to that of the synthetic fibrous structures. The coyote furs have the lowest TC value of 223c 0.046 W/mK at 221210 25e6C. While the TC of all of the samples decreased with temperature, the TC of the natural furs decreased at a higher rate and showed a different behavior with temperature, compared to the synthetic fibrous materials.